A Comparative Study Between Plate Osteosynthesis and Elastic Nailing for Diaphyseal Fracture of Radius and Ulna in Adults - Muhammad, Karwan Sabah; Al-Tamimi, Ali Abdalnabi Alwan (South Eastern European Journal of Public Health, 2024)
Background and Objectives: Diaphyseal fractures of the radius and ulna are common in adults and can be managed with various treatment methods. This study aimed to evaluate and compare the functional, radiological, and clinical outcomes of two treatment methods: plating and intramedullary nailing for diaphyseal fractures of both forearm bones in adults. Methods: This prospective cohort study was conducted in Sulaimani City, Kurdistan, involving 40 adult patients (mean age 34.25 years) who sustained primary diaphyseal fractures of the radius and ulna between January 1, 2022, and June 1, 2024. Patients were divided into two groups: Group A, with 20 patients, underwent closed reduction and internal fixation using flexible intramedullary nailing, while Group B, also with 20 patients, underwent open reduction and internal fixation using 3.5 mm dynamic compression plate. Outcomes were assessed using the Modified Grace Eversmann score, with pronation and supination of the forearm compared to the contralateral side. Results: The mean operation time was 81.4 minutes for the plating group, compared to 62.5 minutes for the nailing group. The mean union time was 13.15 and 10.85 weeks for the plating and nailing groups, respectively. In terms of functional outcomes, 27 patients achieved Excellent scores, 9 Good, 3 acceptable, and 1 unacceptable. Complications occurred in 5 patients in the nailing group and 2 in the plating group. Overall, the union and operation times showed a statistically significant difference, with a higher complication rate in the nailing group. Conclusion: Adults with diaphyseal radius and ulna fractures are usually treated with plating. An alternate fixation method for fracture with distinct risk and benefit profile is intramedullary nailing.